Pengaruh Green Marketing Terhadap Minat beli Yang Dimediasi Oleh Brand Image (Studi Kasus pada Air Minum Dalam kemasan Ades di Toko Panjerejo Tulungagung) - Muchamad Choirul Hisam; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis research aims to identify and analyze the green marketing has a direct impact on directly affected the interest of buying buy water in the ades. Knowing and analyzing the brand image directly affected the interest of buying bottled water in the ades. Establishing and analyzing the influence of green marketing's indirect influence on purchasing interest via the brand image as an intervening variable. The population of this study is the owner of a yulia store that bought Bottled Water by 1229, while samples amounted to 93. Data analysis using path analysis. The technieque employed in this research is sampling techiques . Research has shown that green marketing is a significant and immediate effect equal to 0,842. But green marketing has a direct and significant impact on buying interest equal to 0,854. The brand image is devastating equal to 0,854 and devastating for interest in buying and the brand image can mediate between green marketing's interest in purchasingKeywords: Green marketing, purchasing interests, brand image